A Potential Role for the Myeloid Lineage in Leptin-regulated Bone Metabolism - Scheller, E. L.; Song, J.; Dishowitz, M. I.; Hankenson, K. D.; Krebsbach, P. H. (Hormone and Metabolic Research, 2012)
Leptin influences bone formation centrally through the hypothalamus and peripherally by acting on osteoblasts or their precursors. However, neither mechanism explains the divergent, gender-specific correlation between leptin and bone mineral density in humans. Although leptin is a potent regulator of pro-inflammatory immune responses, a potential role for leptin as an osteoimmunologic intermediate in bone metabolism has not been tested. Mice with myeloid-specific ablation of the long-form leptin receptor (ObRb) were generated using mice expressing cre-recombinase from the lysoszyme M promoter. At 12 weeks of age, the conditional knockout mice did not display any appreciable phenotype. However, at 52 weeks 2 changes were noted. First, there was a mild increase in liver inflammation. Second, a gender-specific, divergent bone phenotype was observed. Female mice displayed a consistent trend toward decreased trabecular bone parameters including reductions in bone volume fraction, trabecular number, and bone mineral content as well as a significant increase in marrow adipogenesis. Conversely, male mice lacked trabecular changes, but had statistically significant increases in cortical bone volume, thickness, and bone mineral density with equivalent total cortical volume. Since the year 2000, over 25 studies on more than 10 000 patients have sought to determine the correlation between leptin and bone mineral density. The results revealed a gender-specific correlation similar to that observed in our LysM transgenic animals. We hypothesize and show new evidence that regulation of myeloid lineage cells by leptin may facilitate their actions as an osteoimmunologic intermediate and contribute to leptin-regulated bone formation and metabolism in a gender-specific manner.
Keywords: osteoimmunology; leptin; bone mineral density; cytokines; macrophages; adipokines